Síntese otimizada de 2-aminocromenos via reação sequencial Knoevenagel-Michael e avaliação da atividade biológica em células tumorais - Abrantes, Poliana Gomes de (2023)
The synthesis of 2-aminochromenes through the sequential Knoevenagel-Michael reaction between salicylaldehydes and malononitrile has generated great interest in the scientific community in recent years, especially for generating new compounds with great structural variety. However, the protocols in the literature still have disadvantages because they have high synthesis times, laborious methods and/or aggressive to the environment. Thus, the present work consists of the investigation and application of solvents for the optimal synthesis of 2-aminochromenes without the need for catalysts, when using salicylaldehydes and malononitrile. Among the solvent tests, the one that stood out the most for the synthesis of 2-aminochromenes 3(a-g) in the proportion 1:2 (salicylaldehyde:malononitrile), in terms of increasing the reaction speed, was the binary mixture ethanol:water (3:7). The binary mixture proved to be more efficient for reactions with aldehydes substituted with electron donating groups whose pure products were obtained in short times (30-40 min) with high yields (90-93%). It was also possible to optimally obtain another class of 2-aminochromenes 4(a-g), in the proportion 1:3 (salicylaldehyde: malononitrile), using only ethanol at reflux. The application of ethanol allowed the synthesis of four new compounds, in addition to three others already known, with short and moderate reaction times (60-300 min) and high isolated yields (75-93%). In addition, this reaction presented high atomic economy, being in accordance with the second principle of Green Chemistry. Compounds 4(a-g) were also tested in vitro in three tumor cell lines to determine their inhibition potentials. The results obtained showed that compounds 4b, 4e and 4f are very promising with an inhibition percentage greater than 75%, with 4e having a selectivity index greater than 2.0 for all cancer cells tested.